Epidemiological Aspects of the Incidence of West Nile Fever in the Republic of Tatarstan in 2023 - M. A. Patyashina; E. P. Sizova; L. G. Avdonina; G. G. Badamshina; L. V. Stavropol’skaya; A. G. Aleshina; I. A. Karpova; A. V. Goncharova; A. R. Nurtdinova; A. S. Antonov (Проблемы особо опасных инфекций)
The aim of the work was to study the epidemiological situation on West Nile fever (WNF) in the Republic of Tatarstan in 2023.Materials and methods. An operational epidemiological analysis of WNF cases registered in the Republic of Tatarstan in 2023 was performed. In order to establish sources and risk factors for infection of the population, 987 samples of zoo-entomological material were examined for the presence of West Nile virus (WNV) markers. A set of laboratory diagnostic methods was used: ELISA, RT-PCR, sequencing.Results and discussion. It has been established that all cases of WNF were registered in the region in the summer-autumn period of 2023, mainly in August, among residents of the city of Kazan who had not traveled outside the Russian Federation and the Republic of Tatarstan over the past six months. The incidence rate of WNF in the Republic of Tatarstan was 0.20 per 100 thousand population, the mortality rate reached 12.5 %. Signs of damage to the central nervous system were present in 6 out of 8 (75 %) patients. The majority of people with severe clinical symptoms belonged to older age groups and had concomitant diseases. Cases of the infection were reported in all age groups, with the exception of children and adolescents. The spatial characteristics of morbidity have been investigated, indicating the diffuse nature of the distribution of cases. The integrated use of methods, consisting in the concurrent use of polymerase chain reaction and enzyme-linked immunosorbent assay, made it possible to laboratory confirm cases of WNF in patients at different stages of the disease. The circulation of a subvariant of the WNV of the second genotype in the Republic of Tatarstan, currently dominant in the southern and central regions of Russia, has been established. A set of measures has been proposed to optimize epidemiological surveillance and control of WNF in the Republic of Tatarstan.